Analysis of Survival and Growth Rates of Young Mangroves - Sabila Martin Dalimunte; M. Taufik Rahmadi; Meilinda Suriani Harefa; Eni Yuniastuti; Zulfajri Zulfajri; Eka Suci Anja Kusumawati; Dewi Permata Sari; Bagus Setiawan (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2026)
Mangrove ecosystems in Indonesia play an important role in coastal protection and biodiversity conservation. However, degradation caused by land-use change and past extreme events has increased the need for effective rehabilitation. Analysis of mangrove growth at an early stage is important because this phase determines the success of long-term restoration. This study aimed to analyze the survival rate and vegetative growth of young mangroves across six coastal villages in Simeulue Regency, Aceh Province, using a comparative site-based approach. Field surveys were conducted in October 2023 using purposive sampling and 1 × 1 m quadrat plots. Observed parameters included survival rate, plant height, stem diameter, species composition, and basic environmental conditions. Results showed significant variation among locations. Tanjung Raya (96.25%), Sambay (93.88%), and Ganting (92.88%) were categorized as highly successful (>80%). Labuan Bakti (68.68%) was moderate, while Pulau Bengkalak (42.15%) and Luan Balu (55.86%) were low. Vegetative growth did not always align with survival rate. Tanjung Raya showed both high survival and strong growth, while Luan Balu exhibited relatively high growth despite lower survival, indicating possible selective environmental pressure. Pulau Bengkalak had both low survival and moderate growth, reflecting ecological constraints. Biotic (crabs, snails), abiotic (tidal dynamics), and anthropogenic (livestock disturbance) factors influenced early mortality. Overall, successful mangrove rehabilitation depends not only on planting efforts but also on site suitability and adaptive local management.